Labeling of food products and purchase decision among staffs of Pejabat Perbendaharaan Negeri Selangor for the year 2008 / Noor Syahidah Saadon - Saadon, Noor Syahidah (Faculty of Business and Management, 2008)
Label in a product is important as it is used by the consumer to refer what are the advantages or even the disadvantages they get if they take the food. This research is about the labeling and purchase decision among staffs of Pejabat Perbendaharaan Negeri Selangor. This research is to identify whether there is a significant relationship between the labeling and the purchase intention with brand, nutrients, halal logo, ingredients, and expiry date.